(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Today, as ecological issues are escalating, providing detailed information not only on TV, radio, and social media but also in written press gains significant importance. This article specifically discusses the issue of writing articles on ecological topics in foreign press.